Prospective intraindividual comparison of automated customized ray-tracing-guided versus wavefront-optimized LASIK - Khoramnia, Ramin; Naujokaitis, Tadas; Blöck, Louise; Fabian, Katharina; Kessler, Lucy Joanne; Łabuz, Grzegorz; Auffarth, Gerd U. (Ophthalmology, 2025)
Purpose - To compare automated customized ray-tracing-guided LASIK with wavefront-optimized LASIK by assessing intraindividual refractive and visual acuity outcomes. - Design - Prospective, interventional, randomized, double-blinded, contralateral-eye comparison. - Participants - Thirty patients (60 eyes) with myopia and myopic astigmatism. - Methods - Ray-tracing-guided LASIK, termed “wavelight plus” (Alcon), was performed in 1 eye and wavefront-optimized LASIK in the fellow eye. For wavelight plus, the ablation profile was calculated automatically by ray-tracing, using only objective measurements obtained with a single diagnostic device. The manifest refraction was used for planning wavefront-optimized LASIK treatment. - Main Outcome Measures - Manifest refraction spherical equivalent (MRSE), refractive cylinder, uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), and safety and efficacy indices were analyzed. The primary end point was the percentage of eyes with an MRSE within ±0.50 diopters (D) at 3 months, tested for noninferiority of wavelight plus. - Results - At 3 months after wavelight plus and wavefront-optimized LASIK, MRSE was within ±0.50 D in 100% (95% confidence interval [CI], 88.6-100) and 90.0% (95% CI, 74.4-96.5) of eyes and within ±0.25 D in 83.3% (95% CI, 66.4-92.7) and 76.7% (95% CI, 59.1-88.2) of eyes, respectively (wavelight plus noninferior for ±0.50 D, P < 0.001; nonsuperior for ±0.25 D, P = 0.625). The mean (± standard deviation) MRSE was -0.05 ± 0.21 D after wavelight plus and -0.16 ± 0.23 D after wavefront-optimized LASIK (P = 0.039). Refractive cylinder and absolute MRSE were similar after both treatments (P > 0.05). The mean monocular UDVA was -0.11 ± 0.07 logarithm of the minimum angle of resolution (logMAR) and -0.09 ± 0.09 logMAR, and the monocular CDVA was -0.14 ± 0.05 logMAR and -0.13 ± 0.06 logMAR after wavelight plus and wavefront-optimized treatments, respectively (P > 0.05). The UDVA was ≥20/20 in 100% (95% CI, 88.6-100) and 93.3% (95% CI, 78.7-98.2) of eyes, and ≥20/16 in 83.3% (95% CI, 66.4-92.7) and 73.3% (95% CI, 55.6-85.8%) of eyes after wavelight plus and wavefront-optimized LASIK, respectively. The efficacy index was 1.01 ± 0.14 and 0.98 ± 0.16, and the safety index was 1.08 ± 0.13 and 1.07 ± 0.14 for wavelight plus and wavefront-optimized LASIK, respectively (P > 0.05). - Conclusions - The automated ray-tracing-guided LASIK treatment wavelight plus had a high safety and efficacy, with visual acuity outcomes comparable to those after wavefront-optimized LASIK. Without the need of manifest refraction, wavelight plus achieved noninferior refractive outcomes and a slightly higher accuracy in MRSE. - Financial Disclosure(s) - Proprietary or commercial disclosure may be found after the references.
Online veröffentlicht: Oktober 2025
Gesehen am 03.02.2026